Literature Review: The Effect of Sun Exposure on Parathyroid Hormone Activity - Rika Dea Puspita; Elsa Yuniarti (Jurnal Biologi Tropis, 2023)
Abstract:Indonesia is one of the tropical countries with year-round sunshine. This certainly allows Indonesians to be regularly exposed to the sun during daytime activities outside the home. Exposure to the sun has a significant impact on humans. To date, research on the prevalence of vitamin D deficiency, particularly in humans, has been rare. The purpose of  this literature review is to provide the reader with information on the effects of sun exposure on parathyroid hormone levels. The method used to write this document is the literary criticism method. (LRA) with references taken from published or revoked (POP) databases published between 2010 and 2022. In this literature review, the keywords used include including sun, hormones, activity, vitamin D, parathyroid glands. Based on literature from a variety of research findings, it was found that sun exposure affects parathyroid hormone levels. Because vitamin D in sunlight is in the  form of 1,25(OH)2D, it works with parathyroid hormone and calcitonin to maintain normal plasma calcium levels.